Analisis Komunikasi Dakwah dalam Lingkungkan Kerja untuk Membangun Karakter Islam Sejak Dini - Pitaloka Pitaloka; Yumna Azkia; Adhi Kusuma (Lembaga Pengembangan Kinerja Dosen, 2025)
Da'wah communication is a form of communication that aims to convey Islamic messages based on the Qur'an and Sunnah in order to form a strong Islamic character. In the context of the work environment, da'wah communication is not only a means of conveying religious values, but also a strategic instrument in building a highly ethical, professional, and spiritual work culture. The success of this da'wah communication is supported by the role of leadership, religious organizational culture, the availability of da'wah media, the active involvement of Muslim employees, and routine religious activities. The obstacles include lack of management support, dense work activities, low employee interest, and limited competence of da'wah actors. Effective strategies in da'wah communication in the work environment include persuasive and humanistic approaches, exemplary behavior (uswah hasanah), and active participation of all elements of the organization. With the implementation of proper da'wah communication, the work environment will not only become a place for professional activities, but also a space for ongoing Islamic character training.